Integrating Bhinneka Tunggal Ika Values into the Multicultural Islamic Education Curriculum: A Love-Based Curriculum Approach - Anjar Subiantoro; Muhammad Imam Syafi'i; Maskuri Bakri (Jayapangus Press, 2026)
Although multicultural Islamic Education has been widely discussed, limited studies have examined how Bhinneka Tunggal Ika values can be systematically integrated into the Islamic Education curriculum through a pedagogy of love, particularly in inclusive school contexts. This study aims to analyze the integration of national unity values into Islamic Education using a love-based curriculum approach as an integrative model for multicultural and inclusive education. Employing a qualitative descriptive library research design, this study analyzes scholarly books, peer reviewed journal articles, and policy documents published over the last decade, selected through purposive sampling. Data were analyzed using content analysis and thematic analysis. The findings reveal three key contributions. First, curriculum adaptation oriented toward affective, relational, and inclusive dimensions enables deeper internalization of diversity values. Second, reflective and empathetic learning strategies such as dialogic reflection, collaborative activities among students with different abilities, and experiential projects effectively cultivate empathy, compassion, and respect for differences. Third, Islamic Education teachers function as central value mediators whose moral exemplarity and empathetic communication foster inclusive learning environments. This study contributes a novel conceptual positioning of the love-based curriculum as an integrative framework linking Islamic values, multicultural education, and inclusive schooling, and offers implications for curriculum development and future empirical research.